ANALISIS EVALUASI PENERAPAN SISTEM INFORMASI PENGOLAHAN NILAI PADA KURIKULUM 2013 DENGAN METODE TAM - Khalifah, Ummi; Pusparini, Nur Nawaningtyas; Kusmawan, Oki (ISTEK WIDURI, 2020)
The purpose of the 2013 Curriculum which is regulated by the Regulation of the Minister of Education and Culture Number 67 of 2013 is to prepare Indonesian people to have the ability to be faithful, productive, creative, innovative, affective and able to contribute to life. In processing values in the 2013 Curriculum, there are 3 (three) assessments such as assessment of students' attitudes, assessment of knowledge, assessment of skills, this is expected to form student character from an early age. However, in the application of the processing, there are several obstacles including some basic competencies that need to be inputted and this takes a long time, besides that the teacher's lack of understanding of IT becomes a challenge when the teacher wants to input data into the system. In the study, the authors used data collection methods such as observation, interviews, questionnaires and literature study. Meanwhile, to evaluate the value processing system using the Technology Acceptance Model (TAM) with 4 parameters such as Perceived Ease of Use, Perceived Usefulness, Attitude Toward using, Behavioral Intention To Use. This method results in showing users believe that the value processing information system with the 2013 curriculum can provide benefits and uses. indicates the user feels confident enough that the system being used is easier to use and operate. shows the great curiosity of the user to use the system. indicates that there is a desire to continue using the system and there is a desire to influence other users to use the system.